Saberes de docentes de educação física acerca dos jogos eletrônicos: implicações para a prática pedagógica na escola - Costa, Adriana da Silva (2024)
Despite the growing scientific production of Electronic Games in school Physical Education, more studies and research are needed to structure better teaching proposals that better use the educational possibilities of this object of knowledge. In this sense, the starting questions of this research were: What are the knowledge and experiences about Electronic Games of Physical Education teachers at school? And what knowledge do teachers need to work with Electronic Games in school Physical Education? The general objective is to: Analyze the knowledge and experiences about Electronic Games of Physical Education teachers and develop teaching material for Physical Education teachers about Electronic Games. This is a qualitative research, in which two groups of Physical Education teachers participated, one group that works in Basic Education and the other that are Higher Education teachers, researchers on Electronic Games at school. Questionnaires and interviews were used to collect data. The data was analyzed based on Content Analysis. It was observed that most of the participating teachers did not have contact with knowledge related to electronic games related to school Physical Education in their initial and continuing training. These teachers stated that the knowledge they have is not enough to develop pedagogical work with Electronic Games at school, however, the data showed that teachers who have some personal experience with games, even without training, are still able to develop this content in school Physical Education. Based on this research, an educational product was developed to help Physical Education teachers who have difficulty intervening with Electronic Games in their classes.